1985
DOI: 10.1080/07391102.1985.10508434
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation on the Sequence Selective Binding of Daunomycin to Double-Stranded Polynucleotides

Abstract: Theoretical computations are performed on the structural and energetical factors involved in the sequence selective binding of daunomycin (DNM) to six representative self-complementary double-stranded hexanucleotides: d(CGTACG)2,d(CGATCG)2,d(CITACI)2, d(TATATA)2, d(CGCGCG)2 and d(TACGTA)2. The conformational angles of the hexanucleotides are fixed in values found in the representative crystal structure of the d(CGTACG)2-DNM complex. The intermolecular DNM-hexanucleotide interaction energies and the conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 38 publications
11
52
1
Order By: Relevance
“…Chen et al (32) have performed computational analysis to model the interaction of daunomycin with six duplex hexanucleotides of defined sequence. They inferred from their calculations that the most energetically favorable binding sites for these antibiotics were the triplet sequences of 5 0 -TCG and 5 0 -ACG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (32) have performed computational analysis to model the interaction of daunomycin with six duplex hexanucleotides of defined sequence. They inferred from their calculations that the most energetically favorable binding sites for these antibiotics were the triplet sequences of 5 0 -TCG and 5 0 -ACG.…”
Section: Introductionmentioning
confidence: 99%
“…They inferred from their calculations that the most energetically favorable binding sites for these antibiotics were the triplet sequences of 5 0 -TCG and 5 0 -ACG. (25,32) However, Chaires et al (25) have shown that the requirement for A or T at the 5 0 end is not absolute and that three contiguous GC base pairs form an acceptable binding site although possibly with weaker binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…The structure is stabilised by several hydrogen bonds. Theoretical calculations [5] suggest that the C9 hydroxyl group forces which would occur between the daunosamine and the 2-amino group of guanine. In order to clarify the importance of these residues for the sequence selective binding we have performed comparative footprinting studies on ditrisarubicin B, which lacks the C13 carbonyl yet possesses an additional charged group on the first sugar attached to C10.…”
Section: Introductionmentioning
confidence: 99%
“…In the second place, intercalators with bulk ligands attached to them, may well have these ligands located in the major as well as in the minor groove. Thus, the 'second generation' anthracyclines, mitoxantrone and anthrapyrazole, while showing a definite specificity for intercalation between GC base pairs, have their side chains located in the major groove [5,61. For these reasons and in view of the potential importance of this new type of drug as an antitumor agent, we have carried out an explicit computation on the stereochemistry of the intercalative are entirely analogous to those used in our studies on the interaction with oligomeric sequences of daunomycin [7], adriamycin [8], mitoxantrone [5] and anthrapyrazole [6] and will thus not be repeated here. Fig.1 recalls the base numbering in the investigated tetramers, the intercalation occurring between bases 2-3' and 3-2'.…”
Section: Introductionmentioning
confidence: 99%